Phenomenology Tools on Cloud Infrastructures using OpenStack - Campos, I. (2013)
We present a new environment for computations in particle physics phenomenology employing recent developments in cloud computing. On this environment users can create and manage “virtual” machines on which the phenomenology codes/tools can be deployed easily in an automated way. We analyze the performance of this environment based on “virtual” machines versus the utilization of physical hardware. In this way we provide a qualitative result for the influence of the host operating system on the performance of a representative set of applications for phenomenology calculations.